HUBUNGAN PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP PERILAKU SOSIAL SISWA DI SD NEGERI KEMUNING JAYA KECAMATAN BELITANG II - Kurnia, Ema; Wahid Hasim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between TikTok social media usage and the social behavior of elementary school students using an exploratory quantitative approach based on the K-Means Clustering algorithm. The research subjects consisted of 50 fifth- and sixth-grade students from several elementary schools selected purposively based on the criterion of actively using TikTok. The instrument used was a closed-ended Likert-scale questionnaire covering two variables: social behavior and TikTok usage. Data were analyzed through several stages, including descriptive statistics, normality testing, Spearman’s correlation, and K-Means clustering to identify patterns between the two variables. The descriptive analysis showed that the mean score of students’ social behavior was 34.12 (SD = 4.274), while the mean score of TikTok usage was 28.30 (SD = 4.087). The correlation analysis revealed a positive relationship, with a Spearman’s coefficient of 0.411 and a significance value of p = 0.003. The clustering analysis produced three clusters: (1) low TikTok usage–low social behavior, (2) moderate TikTok usage–moderate social behavior, and (3) moderate usage–high social behavior. This pattern indicates a positive and consistent relationship between the two variables. Therefore, it can be concluded that TikTok usage, in certain contexts, may contribute to the development of students’ social behavior, although it is also influenced by other external factors.